The artful mind : cognitive science and the riddle of human creativity - Turner, Mark, 1954- (OUP E-Books., 2006)
All normal human beings alive in the last fifty thousand years appear to have possessed, in Mark Turner's phrase, "irrepressibly artful minds." Cognitively modern minds produced a staggering list of behavioral singularities--science, religion, mathematics, language, advanced tool use, decorative dress, dance, culture, art--that seems to indicate a mysterious and unexplained discontinuity between us and all other living things. This brute fact gives rise to some tantalizing questions: How did the artful mind emerge? What are the basic mental operations that make art possible for us no